Evolutionary selection for protein aggregation. (19th September 2012) - Sanchez de Groot, Natalia; Torrent, Marc; Villar-Piqué, Anna; Lang, Benjamin; Ventura, Salvador; Gsponer, Jörg; Babu, M. Madan
Abstract : Protein aggregation is being found to be associated with an increasing number of human diseases. Aggregation can lead to a loss of function (lack of active protein) or to a toxic gain of function (cytotoxicity associated with protein aggregates). Although potentially harmful, protein sequences predisposed to aggregation seem to be ubiquitous in all kingdoms of life, which suggests an evolutionary advantage to having such segments in polypeptide sequences. In fact, aggregation-prone segments are essential for protein folding and for mediating certain protein–protein interactions. Moreover, cells use protein aggregates for a wide range of functions. Against this background, life has adapted to tolerate the presence of potentially dangerous aggregation-prone sequences by constraining and counteracting the aggregation process. In the present review, we summarize the current knowledge of the advantages associated with aggregation-prone stretches in proteomes and the strategies that cellular systems have developed to control the aggregation process.